THE ROLE OF BKPSDM IN HANDLING CASES OF ASN DISCIPLINE VIOLATIONS (CASE STUDY OF PRINCIPAL'S ABSENCE AT STATE ELEMENTARY SCHOOL 01 KOTAWARINGIN TIMUR CENTRAL KALIMANTAN) - Rizka Amanda, Rizka; Fadhila, Amanda Fathona; Aprilia, Zahra Utami; Haptoro, Dyanzah Aji; Hafizah, Desi (jurnal.unprimdn.ac.id, 2025)
The Human Resources Development and Civil Service Agency (BKPSDM) strategically handles disciplinary violations of State Civil Apparatus (ASN) by Government Regulation 94 of 2021 concerning Civil Servant Discipline. This study aims to analyze the role of BKPSDM in handling cases of ASN disciplinary violations, focusing on a case study of the absence of a school principal in the East Kotawaringin Regency. The research method used is qualitative, with data collection techniques through interviews, document studies, and observations. The study results show that BKPSDM plays a role in receiving reports of violations, conducting initial investigations, providing recommendations for sanctions, and providing guidance to ASNs who violate discipline. In addition, there are obstacles in the handling process, such as limited evidence and coordination between agencies. This study concludes that the role of BKPSDM is significant in enforcing ASN discipline, but it is necessary to improve the supervision mechanism and synergy between stakeholders to prevent similar violations in the future.